Water Depth Monitoring based on Affordable Modem to Prevent Flooding and Wildfires, Study Case in Teluk Seruo Lake, Indonesia - Khairul Saleh; Rendy M. Wahid; Hadi; Iskhaq Iskandar; Adnan, Assaidah (Science and Technology Indonesia, 2025)
A cutting-edge telemetry system for water depth monitoring is essential for achieving effective and reliable measurements through bidirectional communication. This system is designed to operate at any time requested by the user, enhancing the relevance of the collected data while promoting significant energy and memory savings. We propose implementing this innovative design at a Teluk Seruo Lake, featuring advanced flood and drought warning functions to proactively address the challenges of seasonal natural disasters. Using an Arduino board paired with an ultrasonic sensor and equipped with a Wi-Fi modem, users can seamlessly communicate with their smartphones to initiate measurements and access real-time water depth data via a dedicated website. Our laboratory tests confirm that timely alerts were successfully sent to users’ phones whenever water levels exceeded critical thresholds. Furthermore, during field tests, continuous monitoring of the lake’s water depth was efficiently conducted through the website, powered by 8400 mAh batteries that supported up to 75 data transmissions over a 12.5-hours period. This remarkable performance establishes a solid baseline for modem power consumption, underscoring the system’s effectiveness and reliability.